Depending on size and weight of native and alien species of amphipods (Аmphipoda, Сrustacea) on the territory of Belarus - Makaranka, Andrei I. (Journal of the Belarusian State University. Ecology, 2019)
The ratio between the raw and dry mass and the dependence of these parameters on the length of the body for foreign Echinogammarus ischnus (Stebbing, 1899), Echinogammarus trichiatus (Martynov, 1932), Chelicorophium curvispinum (G. O. Sars, 1895), Chelicorophium robustum (G. O. Sars, 1895 ), Dikerogammarus haemobaphes (Eichwald, 1841), Dikerogammarus villosus (Sowinsky, 1894), Obesogammarus crassus (G. O. Sars, 1894), Obesogammarus obesus (G. O. Sars, 1896), Pontogammarus robustoides (G. O. Sars, 1894) and native Gammarus lacustris Sars, 1863, Gammarus varsoviensis Jazdzewski, 1975 species of amphibious crustaceans (Amphipoda) from water bodies and streams of Belarus. The comparison showed that the obtained equations for alien species did not show significant differences from those presented in the literature for populations from the original range. The equations for native species differ from each other, and also differ from the literature data, which requires further analysis.